(untitled) (Research, Society and Development, 2020)
Objective: to identify in the world literature the barriers that pregnant refugees and immigrants encounter in destination countries. Materials and Methods: Integrative review, with data collection performed in 2019 by searching the databases of the Virtual Health Library and Pubmed (Biblioteca Virtual de Saúde - BVS) and Pubmed, from 2014 to 2018, including articles publishe from year 2014 to 2018, according to the PRISMA method. Minayo’s proposal was used for the analysis. Results: the final sample consisted of 11 articles. Sample analysis generated five predominant themes: “communication”, “support network”, “cultural and religious diversity and intolerances”, “public policies and health systems” and “healthcare team”. Conclusions: The listed themes are crucial to outline a strategy of welcoming, service and quality care that guarantee the necessary and dignified support to inmigrant and refugee pregnant women.